Where will they go if we go territorial? Dividend exemption and the location decisions of US multinational corporations - Rosanne Altshuler; Harry Grubert (Rutgers University, Department of Economics, 2002)
We approach the question of how moving to a dividend exemption system would affect the location incentives of U.S. corporations from three different angles. We start by comparing the U.S. allocation of foreign direct investment in manufacturing across low-tax versus high-tax jurisdictions with that of two major dividend exemption countries, Germany and Canada. The second section demonstrates how the effective tax rate on the typical investment in a low-tax affiliate would change under a dividend exemption system. The final approach uses data from the tax returns of U.S. multinationals to gauge how location decisions will be affected. Taken together, the analysis provides no consistent or definitive evidence that location decisions would be significantly changed if dividends were to be exempt from U.S. corporate tax.
Keywords: H25; H87; 330; cost of capital; dividend exemption; international taxation; multinationals; territorial taxation